Peran Manager Sumber Daya Manusia (SDM) dalam Keputusan Strategis untuk Program Pelatihan dan Pengembangan - Anandita Desmaningtyas; Marsa Batrisya Bazla; Saphira Cerelia Dewi; Aurelia Azizah Fatika; Rusdi Hidayat; Indah Respati Kusumasari; Nugraha Kusbianto (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to examine the role of human resource managers in strategic decision-making regarding employee training and development programs. The research method used is a literature study that analyzes various relevant theories and previous research findings. The results indicate that the role of HR managers has shifted from administrative functions to strategic business partners who are responsible not only for implementing training programs but also for long-term planning based on competency needs analysis. Factors such as leadership support, organizational culture, resource availability, and technological advancement significantly influence the quality of strategic HR decisions. Well-aligned and data-driven decisions enhance training effectiveness, employee motivation, and organizational productivity. This study highlights the importance of analytical capability, adaptive leadership, and digital technology utilization for HR managers to develop relevant and competitive training policies. The findings are expected to serve as a reference for organizations in formulating more targeted human resource development strategies that positively impact overall organizational performance.